Pengaruh Viral Marketing Dan Brand Image Terhadap Minat Beli Produk Somethinc Di Platform Tik Tok Shop (Studi Kasus Pada Para Pengguna Tik Tok di Wilayah Bekasi Timur) - Lisnawati, Lisnawati; Susmonowati, Trinik (JAMBIS : Jurnal Administrasi Bisnis, 2025)
Maintaining healthy skin is a positive lifestyle that everyone does regularly. Generally, what happens to a woman, it has become an urge for them to always look beautiful and be the main of everyone's attention. Healthy skin is one of the important points for all communities. The diversedemands in caring for the skin drive skincare businesses to innovate in theirproducts; all of this is done to make it easier for consumers to choose self-care products. This study aimed to examine the influence of viral marketingand brand image have on buying interest in Somethinc products on the TikTok Shop platform. This research used quantitative methods and data obtained through distributing questionnaires. The sample in this study werecustomers who had purchased Somethinc products and obtained 120respondents. Data analysis used multiple linear regression. The results of this study indicated that Viral Marketing (X1) partially has a positive and significant effect on Purchase Intention (Y) for Somethinc Products on the TikTok Shop Platform by 53,5%. Partially, Brand Image (X2) has a positiveand significant effect on Buying Interest (Y) in Somethinc Products on the TikTok Shop Platform by 81,3%. Viral Marketing (X1) and Brand Image (X2)together have a positive and significant effect on Buying Interest (Y) in Somethinc Products on the TikTok Shop Platform by 88% and the remaining 12% is influenced by other variables not examined.